2016
DOI: 10.1044/2016_jslhr-h-15-0363
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Measures of Hearing Loss and Tinnitus in Pediatric Cancer and Hematopoietic Stem Cell Transplantation: A Systematic Review

Abstract: Purpose We identified studies that described use of any patient-reported outcome scale for hearing loss or tinnitus among children and adolescents and young adults (AYAs) with cancer or hematopoietic stem cell transplantation (HSCT) recipients. Method In this systematic review, we performed electronic searches of OvidSP MEDLINE, EMBASE, and PsycINFO to August 2015. We included studies if they used any patient-reported scale of hearing loss or tinnitus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…31 However, no validated PRO instrument exists for tinnitus in pediatric patients despite multiple calls for their development. 25,26,[32][33][34] Until such an instrument is available, other changes in practice, such as a checklist system for symptoms related to treatment exposures or obtaining the review of systems through a patient-completed questionnaire, might improve screening and earlier detection of tinnitus in CCS without requiring the additional health care costs more frequent audiologic evaluation would entail. 35,36 In summary, documented screening and detection of tinnitus by survivorship providers is inadequate, even among high-risk CCS.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, no validated PRO instrument exists for tinnitus in pediatric patients despite multiple calls for their development. 25,26,[32][33][34] Until such an instrument is available, other changes in practice, such as a checklist system for symptoms related to treatment exposures or obtaining the review of systems through a patient-completed questionnaire, might improve screening and earlier detection of tinnitus in CCS without requiring the additional health care costs more frequent audiologic evaluation would entail. 35,36 In summary, documented screening and detection of tinnitus by survivorship providers is inadequate, even among high-risk CCS.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that single questions such as “Do you have a problem with your hearing?” are less able to detect mild hearing loss than more comprehensive instruments like the Hearing Handicap Inventory for the Elderly—Screening Version (HHIE-S) [30]. A recent systematic review that described patient-reported measures for hearing loss identified only two instruments, the Health Utilities Index (HUI) [31] and the Hearing Measurement Scale (HMS) [32] that are used with childhood cancer patients [33]. The HUI includes six questions, the HMS 44 questions, and both return hearing-specific summary scores.…”
Section: Discussionmentioning
confidence: 99%
“…The HUI includes six questions, the HMS 44 questions, and both return hearing-specific summary scores. Researchers reported that none of the questionnaires appeared ideal based upon the number of questions, and wording for children or adolescents, and psychometric properties were never tested in this population [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Important aspects of novel hearing restoration strategies including gene therapy [3], stem cells [4,5], and related intracochlear distribution nanotechnologies [6,7] are still at best in a preclinical phase.…”
Section: Introductionmentioning
confidence: 99%